FAILURE ANALYSIS OF GAS TRANSMISSION PIPELINE GRADE API 5L X-52 CAUSED BY GEOHAZARD SOIL MOVEMENT LOAD AND EROSION BY THE RIVER FLOW - OCTAVIANUS (NIM 12104026); Pembimbing: Dr. Ir. Syoni Soepriyanto, M. Sc., dan Dr. Ahmad Taufik, ANDRY
Pipeline is a system which is used to transport fluid (oil and gas) from one place to another. If the pipeline get broken caused by failed material it can give a big loss both for company and consumer. The accident happened to the gas transmission pipeline on 2007 which was installed in 1976. The line pipe conformed to API 5L X-52 grade material. It is buried when installed and located near the river. The soil under the pipe is eroded by the river flow which is used to support the pipe. At the same time the pipe get a load from the soil above it, give a deformation then brittle fracture on welded area. After that, the broken pipe is replaced with the new one then support is given to the new line pipe but after a year the line pipe is moved from the support which proof that there are big geohazard at the area. Failure analysis will be applied on that broken pipe in order to find the main cause and mechanism of pipe failure. Broken pipe will be analyzed based on some information. First, the information get from field survey is about the pipe in general and doing a visual investigation at the pipeline location. After that the other thing to do is sampling, then doing some mechanical and chemical testing on it then studying about the microstructure of the line pipe material. Stress analysis calculation is needed to analyze an external load of the pipe and erosion which occurred inside the pipe. Based on field survey result, geohazard is the main cause of linepipe failure and the result is brittle fracture. The results from laboratory testing are hardness profile and chemical composition. Then, based on hardness to tensile conversion, the UTS is 458 MPa. Microstructure of HAZ shown by microscope observation result which has significant increase hardness in HAZ is martensite which have a great hardness but brittle. Based on analytical calculation, external stress of pipe is 653 MPa. The stress concentration factor in welded area is 1.8 so welded area stress is 1175.4 MPa which is big enough to generate failure. Metal loss caused by erosion and internal corrosion which was occurred inside the linepipe. The final conclusion is fracture occurred in the brittle HAZ area where was caused by soil movement load that create brittle fracture along welded area. The alternative solution to overcome this problem is made based on field survey report, laboratory testing and analytical calculation. The solution is re-routing the pipeline to minimize the geohazard effect.